PELATIHAN DIGITAL MARKETING DAN PEMBERDAYAAN UMKM DESA KATIALADA - Kartika, Dewy; Kadir, Rahmawati; Mahmud, Sri; Bagu, Miranda; Taliki, Muhammad; Popa, Alvian; Entengo, Abd.; Ismail, Indriati; Kaunang, Narti (Universitas Gorontalo, 2024)
The existence of MSMEs as the driving force of the national economy has proven to be very contributing and its role in absorbing more workers than other businesses. Common problems that are always faced by MSME actors are limited capital, human resources that are less competent in their fields and the use of technology. This study aims to conduct Diigital Marketing training such as creating Shoppe and Instagram accounts as a form of empowering MSMEs in Katialada Village so that MSMEs in Katialada Village can develop well and can be known by the wider community. The method used in this study is direct observation with the coordinator of MSMEs in Katialada Village and continued with training on the creation and use of shopee and Instagram accounts. The result of this study is that MSMEs in Katialada Village have gained knowledge to analyze their business feasibility, especially in the aspect of online marketing, the use of shopee and Instagram accounts has begun to be optimized by MSME players and MSME players are increasingly motivated and enthusiastic in marketing products online.Keywords : Training, online, UMKM